What is the Impact of AI Agents and Agentic AI in the Field of Marketing Management? - Maria Joy Casano Iglesia; Rai Rake Setyawan (Bincang Sains dan Teknologi, 2025)
The rapid advancement of artificial intelligence (AI) has transformed marketing management from a predominantly human-centered decision-making domain into a hybrid ecosystem where intelligent agents and agentic AI systems increasingly assume autonomous roles. This opinion-based article critically examines the impact of AI agents and agentic AI on marketing management, emphasizing their transition from decision-support tools to semi- and fully autonomous decision-makers. Drawing on contemporary literature, this study argues that AI agents reshape strategic, operational, and relational dimensions of marketing by automating complex decisions, enabling agentic personalization, and redefining marketer–consumer relationships. Using a conceptual framework grounded in autonomy theory and the marketing mix, the article synthesizes existing research to highlight opportunities, risks, and managerial implications. The findings suggest that while agentic AI enhances efficiency, scalability, and responsiveness, it simultaneously raises ethical, governance, and consumer autonomy concerns. This article contributes to marketing management scholarship by integrating classic and emerging perspectives on AI agents into a coherent analytical narrative relevant for researchers and practitioners.